1999
DOI: 10.1046/j.1523-1755.1999.055003945.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil prevents the progressive renal failure induced by 5/6 renal ablation in rats

Abstract: tration with CD43-and ED1-positive cells in glomeruli and Mycophenolate mofetil prevents the progressive renal failure interstitium was two to five times lower in MMF-treated rats induced by 5/6 renal ablation in rats.(P Ͻ 0.01). Expression of adhesion molecules CD18 and CD11b Background. Extensive renal ablation is associated with prowas similarly reduced. gressive sclerosis of the remnant kidney. Because lymphocytes Conclusion. MMF ameliorates the progressive renal damage and monocytes accumulate in the remn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
144
2
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 23 publications
11
144
2
7
Order By: Relevance
“…It is interesting that IL-10 was associated with an approximately 50% reduction in this inflammatory response. The possibility that this could be one of the renoprotective mechanisms for IL-10 in this model is supported by a similar study in which treatment of the remnant kidney model with mycophenolate mofetil also reduced macrophage and T cell infiltration with functional and histologic improvement (16).…”
Section: Discussionmentioning
confidence: 63%
“…It is interesting that IL-10 was associated with an approximately 50% reduction in this inflammatory response. The possibility that this could be one of the renoprotective mechanisms for IL-10 in this model is supported by a similar study in which treatment of the remnant kidney model with mycophenolate mofetil also reduced macrophage and T cell infiltration with functional and histologic improvement (16).…”
Section: Discussionmentioning
confidence: 63%
“…The MSC-treated animals showed less fibrosis, but they had a reduced glomerulosclerosis index. These partially improved outcomes were also seen following other therapeutic strategies, such as MMF therapy, using the remnant model, where glomerular and interstitial injuries were attenuated despite persistent proteinuria [13,41]. Interestingly, anemia was also reduced in MSC-treated animals.…”
Section: Discussionmentioning
confidence: 67%
“…This drug can ameliorate renal dysfunction and proteinuria associated with fewer areas of segmental sclerosis and interstitial fibrosis, by and reducing ED-1 À , CD43 À , CD18 À , and CD11b þ infiltrating cells [11,12]. However, glomerular hypertrophy and systemic hypertension remained unchanged [13]. Thus, more robust therapies are necessary to halt CDK progression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, different groups showed that MPA reduces the extent of interstitial fibrosis and glomerular sclerosis also in the 5/6-nephrectomy model, a non-immune-mediated model of progressive renal damage. 22,[33][34][35] To investigate the possible biologic mechanisms underlying the clinical action of this immunosuppressive drug, we decided to apply an exploratory genomic analysis performed as an hypothesis-generating approach. The transcriptomic screening has been extensively used in transplantation to identify biomarkers for an early diagnosis of acute 36 and chronic rejection, 37 but presently, little is known about the change in the genomic profile induced by pharmacologic intervention in transplant recipients.…”
Section: Discussionmentioning
confidence: 99%